1982
DOI: 10.1002/ar.1092020109
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes during stimulation of amphibian oxyntic cells viewed by scanning and transmission electron microscopy

Abstract: Amphibian oxyntic cells exposed by cryofracture were examined by field emission scanning electron microscopy. Comparisons were made between the structure thus revealed and those seen in thin-sectioned material from the same mucosas examined by transmission electron microscopy. Resting oxyntic cells had apical surfaces which were relatively smooth with some short microvilli. Apical cytoplasm was filled with smooth membrane tubules (so-called vesicotubules). Stimulation with a combination of histamine, dibutyryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

1983
1983
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
(43 reference statements)
1
6
1
Order By: Relevance
“…In fasting conditions, the cytoplasm of these cells is filled with a conspicuous tubulovesicular membrane system. The apical surface is covered with short microvilli (Logsdon and Machen 1982).…”
mentioning
confidence: 99%
“…In fasting conditions, the cytoplasm of these cells is filled with a conspicuous tubulovesicular membrane system. The apical surface is covered with short microvilli (Logsdon and Machen 1982).…”
mentioning
confidence: 99%
“…This model bears some analogy to the one proposed by Logsdon and Machen (1982) for the oxyntico-peptic cells of amphibians, which involves the lateral fusion of the tubules with the apical zone of the cell and the consequent formation of cytoplasmic lamellae. It requires the presence of a cytoplasmic matrix which is capable of complex changes in coordination with those of the cytomembranes.…”
Section: The Mode Of Development Of the Intracellular Canaliculusmentioning
confidence: 60%
“…Ultrastructural studies of amphibian oxyntic cell have been reported by numerous investigators including (Vial and Orrego, 1960;Sedar, 1961Sedar, , 1965Sedar, , 1969Lillibridge, 1968;Forte and Forte, 1971;Carlisle et al, 1978;Logsdon and Machen, 1982). There is general agreement that the resting oxyntic cell has only a few short microvilli and the small lumen may be packed with a granular substance.…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, changes in the cytoplasmic membrane system of the resting frog oxyntic cell leading to membrane rearrangement during early stages of histamine stimulation were examined by the method used for the rat stomach. An earlier report on amphibian oxynticopeptic cells by routine SEM methods (Logsdon and Machen, 1982) shows little detail in the cytoplasm. In our study the membranes were clearly visualized because the cytoplasmic matrix was removed by the aldehyde-osmium-DMSO-osmium (A-ODO) method (Tanaka and Mitsushima, 1984).…”
Section: Tem Scanning Electron Microscopymentioning
confidence: 94%